Application of Simple Moving Average in Predicting Operational Expenditure at PT. Tri Tunas Unggul - Lunardi, Louis; Hayati, Nahrul; Handayani, Lilies (LPPM-ITEBA, 2025)
This research aims to analyze and predict operational expenditure patterns at PT. Tri Tunas Unggul using the Simple Moving Average (SMA) method. The research data consists of daily operational expenditure records from July to October 2024. The analysis employs two SMA periods, 7-day and 30-day intervals, to identify both short-term and long-term expenditure trends. The results show that the 7-day SMA provides more responsive tracking of changes in daily expenditures, while the 30-day SMA reveals more stable long-term trends. The analysis identifies three significant peaks in the 7-day SMA in early August, late September, and mid-October, indicating cyclical spending patterns. This research demonstrates that the SMA method can be effectively utilized as a financial analysis tool to support decision-making in managing operational costs and investment strategies at PT. Tri Tunas Unggul.